2021
DOI: 10.1016/j.burns.2020.06.005
|View full text |Cite
|
Sign up to set email alerts
|

A review of burn symptoms and potential novel neural targets for non-invasive brain stimulation for treatment of burn sequelae

Abstract: Burn survivors experience myriad associated symptoms such as pain, pruritus, fatigue, impaired motor strength, post-traumatic stress, depression, anxiety, and sleep disturbance. Many of these symptoms are common and remain chronic, despite current standard of care. One potential novel intervention to target these post burn symptoms is transcranial direct current stimulation (tDCS). tDCS is a non-invasive brain stimulation (NIBS) technique that modulates neural excitability of a specific target or neural networ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 128 publications
(142 reference statements)
0
2
0
1
Order By: Relevance
“…Hosseini et al reported that modulation of the sensory cortex with transcranial direct current stimulation reduced pain and anxiety during burn scar treatment [ 41 ]. A review article also indicated that changes in cerebral activation during non-invasive brain stimulation were associated with improvements in pain symptoms, pruritus, depression, and sleep disturbances caused by burns [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hosseini et al reported that modulation of the sensory cortex with transcranial direct current stimulation reduced pain and anxiety during burn scar treatment [ 41 ]. A review article also indicated that changes in cerebral activation during non-invasive brain stimulation were associated with improvements in pain symptoms, pruritus, depression, and sleep disturbances caused by burns [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Se ha documentado la reducción de dolor, mejora en la función motora y las capacidades cognitivas y como tratamiento de la depresión. Actualmente, la información científica sobre esto se encuentra muy reducida en la literatura y se requieren más estudios para conocer con amplitud sus beneficios sobre dolor en estos pacientes (15).…”
Section: Opioidesunclassified
“…The skin is the first to be damaged by the action of an exogenous burn factor, and secondary changes occur in all body systems [13,15]. At thermal defeat, there is a neuro-pain syndrome, and also emergence in blood plasma of burn toxins, peptides of average molecular weight which provoke development of endogenous intoxication and cause disturbances of blood circulation and morphological reorganization of neuroendocrine bodies, in particular, a cerebellum which is a target under the influence of factors of different origin [4,14]. This organ of the central nervous system is a multifunctional component of the brain, which is responsible not only for motor control, but participates in cognitive functions, afferent and behavioral reactions, the dynamics of emotional and mental state, their changes [3,19].…”
Section: Introductionmentioning
confidence: 99%